2015
DOI: 10.1002/mrd.22493
|View full text |Cite
|
Sign up to set email alerts
|

Non‐hormonal targets underlying endometriosis: A focus on molecular mechanisms

Abstract: Endometriosis is regarded as a hormone-dependent disease. Current therapeutic approaches to treating this common gynecological disorder mainly depend on surgical and hormonal interventions, but the high rate of disease recurrence as well as the side effects related to such therapies make it difficult for patients to recover completely. Molecular evidence has recently suggested that the source of endometriosis can be both hormone-dependent and influenced by the dysregulation of some signaling cascades. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 178 publications
(174 reference statements)
0
1
0
Order By: Relevance
“…A study showed that not only the dysregulation of signaling pathways but also cytokines may trigger the formation of endometriosis [ 28 ]. The phosphatidylinositol-3 kinase (PI3K)/protein kinase B (AKT) signaling pathway is a pivotal intracellular signal transduction pathway, and the function of this pathway is the maintenance of the physiological functions [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that not only the dysregulation of signaling pathways but also cytokines may trigger the formation of endometriosis [ 28 ]. The phosphatidylinositol-3 kinase (PI3K)/protein kinase B (AKT) signaling pathway is a pivotal intracellular signal transduction pathway, and the function of this pathway is the maintenance of the physiological functions [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although normal and ectopic endometrium are histologically similar, endometriotic lesions show a dysregulated response to ovarian steroids [ 70 , 71 ]. Oestrogen (E2) and progesterone are the master regulators of endometrial tissue.…”
Section: The Role Of Mtor Pathway In Endometriosis and Endometriosis-...mentioning
confidence: 99%
“…Over the past decade, cumulative evidence has implicated certain intracellular signalling pathways dysregulation in the molecular pathogenesis of endometriosis [ 71 ]. The mTOR pathway has been extensively studied as a potential pathway underpinning the initiation and development of endometriosis [ 75 ].…”
Section: The Role Of Mtor Pathway In Endometriosis and Endometriosis-...mentioning
confidence: 99%